The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1678-4766e2017122
|View full text |Cite
|
Sign up to set email alerts
|

Vespas Spheciformes (Hymenoptera, Apoidea) do Mato Grosso do Sul, Brasil

Abstract: ABSTRACT. Spheciformes Wasps (Hymenoptera, Apoidea) from Mato Grosso do Sul, Brazil. Here we present a species list of spheciformes wasps of the families Ampulicidae, Sphecidae and Crabronidae, registered in west and southwest of the Mato Grosso do Sul state, Brazil. The surveys were conducted in 22 sampling points, with emphasis on Serra da Bodoquena region, covering the biomes: Cerrado, Atlantic Forest and Chaco. We recorded 506 individuals distributed in 47 genera and 109 species. Trypoxylon Latreille was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although the diversity of wasps is certainly higher and more sampled in the present study, the number of bee species known to Mato Grosso do Sul indicates that this group is best studied at this moment (Auko & silvestre 2013;Moure et al 2013;Auko et al 2017;liMA & silvestre 2017;luz et al 2017;shiMbori et al 2017;trAd & silvestre 2017).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although the diversity of wasps is certainly higher and more sampled in the present study, the number of bee species known to Mato Grosso do Sul indicates that this group is best studied at this moment (Auko & silvestre 2013;Moure et al 2013;Auko et al 2017;liMA & silvestre 2017;luz et al 2017;shiMbori et al 2017;trAd & silvestre 2017).…”
Section: Discussionmentioning
confidence: 65%
“…The current knowledge of Hymenoptera in the state of Mato Grosso do Sul comprises about 386 species (260 nominal) in 107 genera of bees (Moure et al 2013;liMA & silvestre 2017), and at least 420 species in 286 genera of wasps (Auko & silvestre 2013;Auko et al 2017;luz et al 2017;shiMbori et al 2017;trAd & silvestre 2017). However, many of these records are generic identifications, and some of these are outside the Pantanal biome.…”
mentioning
confidence: 99%
“…The preference of smaller diameter orifices for nest building and provisioning may reflect behavioral strategies adopted to minimize energetic expenditure in relation to the morphological characteristics and body structure of each species, which presumably replicates the wasps' behavior in their natural environment. Furthermore, Trad and Silvestre (2017) found that most wasp species are correlated with a specific type of phytophysiognomy, and that the distribution and diversity of these wasps are determined by the heterogeneity of habitats, their spatial arrangement, the availability of resources, including nest-building materials, and land use. Aguiar and Martins (2002) concluded that the occupation of larger orifices would require the expenditure of more energy and material for the construction of the nest, with the preference for a given diameter reflecting the body size of the female wasp.…”
Section: Página | 1163mentioning
confidence: 99%